Macrofocal multiple myeloma in the era of novel agents in China - Xuelin Dou; Ruixia Liu; Yang Liu; Nan Peng; Lei Wen; Daoxing Deng; Leqing Cao; Qian Li; Liru Wang; Fengrong Wang; Xiaodong Mo; Jin Lu (Therapeutic Advances in Hematology)
Background: Macrofocal multiple myeloma (MFMM) is characterized by clonal plasma cells comprising less than 20% of the bone marrow, multiple lytic bone lesions, and the absence of anemia, renal insufficiency, and hypercalcemia. This subtype of multiple myeloma (MM) has a relatively low incidence. Prognostic staging and cytogenetic guidance for MFMM are often insufficient due to the low tumor burden in the bone marrow. Large cohort studies on this subgroup during the era of novel agents are limited. Objectives: We aim to describe the clinical characteristics and prognostic markers of MFMM patients undergoing treatment with novel agents. Methods: Consecutive cases of MM patients diagnosed at Peking University People’s Hospital and Fu Xing Hospital of Capital Medical University from 2011 to 2023 were screened. A propensity score matching was conducted with a 2:1 ratio, matching classic MM patients to MFMM patients based on clinical variables of age and year of diagnosis. Results: We identified 91 cases (4%) of MFMM and 182 matched classic MM among 2291 MM patients. The MFMM cohort had a higher proportion of male patients, those with <90% clonal plasma cells in the bone marrow by multiparameter flow cytometry, and patients with extramedullary disease, along with a lower proportion of patients with high-risk cytogenetics or advanced disease staging. MFMM patients demonstrated better overall responses compared to the control cohort ( p = 0.027) in those not receiving upfront autologous stem cell transplantation (ASCT). During a median follow-up of 42.8 months for the entire cohort, the MFMM cohort exhibited significantly superior progression-free survival (PFS) and overall survival (OS) compared to the control cohort. In multivariate analysis of the entire cohort, exposure to immunomodulatory drugs and ASCT consolidation in frontline therapy were independently associated with improved PFS and OS. For the MFMM cohort, a Ki-67 index ⩾20% was associated with inferior PFS, providing valuable prognostic information in a group where staging and cytogenetic guidance are often inadequate. Conclusion: We concluded that treatment strategies for MFMM patients should align with those for standard MM, and a Ki-67 index ⩾20% in biopsy samples of plasmacytoma is associated with inferior PFS.